Characterization of polymeric nanoparticles - Khan, Sabir [UNESP]; Wong, Ademar [UNESP]; Zeb, Shakeel [UNESP]; Mortari, Bianca [UNESP]; Villa, Javier E.L. [UNESP]; Sotomayor, Maria D.P.T. [UNESP] (Elsevier, 2022)
Polymeric nanoparticles (PNPs) are solid colloidal particals ranging in size from 10 to 1000nm(1µm), and these are broadly used due to their exceptional properties and high surface areas. Polymeric-based nanoparticles competently take drugs, DNA, and proteins to their target cells or organs. Owing to their nanosize, the stability of dosage is a big issue, and it also requires excellent manufacturing skills, sophisticated technology, and also expensive industrial application. The fabricated materials are characterized by transmission electron microscopy, scanning electron microscopy, atomic force microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, zeta potential, nuclear magnetic resonance spectroscopy, and differential scanning calorimetry. Polymer nanoparticles have received increased attention worldwide due to extensive range of use in multidisciplinary fields such as analytical chemistry, physics, electronics, biopharmaceutics, and biology. This chapter covers the general elucidation of PNPs, its synthesis, characterization and its applications in pesticides, environmental, textile, medicine and other industries.
Keywords: application; characterization; Polymeric nanoparticles